Efeitos de múltiplos predadores e complexidade de hábitat na sobrevivência de Oreochromis niloticus - Moura, Maria Joana Nogueira de (Universidade Federal Rural do Semi-Árido, 2016)
The introductions of non-native animal species occur in all regions colonized by man and has caused a number of changes in native communities, mainly eliminated several species of fish that are present in the environment and serve as food for other fish, so the aim of this work was to evaluate the effect of two predators, Cichla kelberi and Hoplias aff. malabaricus in the presence of artificial macrophytes on the survival of the prey niloticus. The study was conducted in an experiment with a completely randomized design in which it was used two levels of macrophytes (with and without) and three levels of predators (H. aff. malabaricus, C. kelberi, and H. aff. malabaricus + C. kelberi) with 5 replicates each, beginning with the addition of 70 tilapia by closing the tank and after 24 hours by counting the proportion of prey consumed. The analysis of the effect of predators and the presence of artificial macrophytes in the proportion of prey consumed as well as the interaction of these factors was assessed by the factorial analysis of variance (two-way ANOVA) and to calculate the expected effects additives and multiple predators multiplicative own equations of the models were used. Based on these analyzes it was identified that C. kelberi and H. aff. malabaricus consumed similar proportions of O. niloticus in monospecific treatments. In environments with artificial macrophytes average of prey consumed was significantly lower for the treatment with the predator C. kelberi. The effects observed and expected multiple predators were not significant, but for the treatments with artificial macrophytes was and was not identified emerging impact of multiple predators for any environment. Finally, this work showed that the successful establishment of invasive O. niloticus species may be favored in environments containing artificial macrophytes, as well as the interaction between predators in which once together reduced the mortality rate of non-native prey
Effects of multiple predators and habitat complexity in the survival of Oreochromis niloticus
Keywords: Fish; Artificial macrophytes; Oreochromis niloticus; Pescado; Macrófitas artificiais; Oreochromis niloticus; CIENCIAS AGRARIAS::MEDICINA VETERINARIA